2001
DOI: 10.1021/es010808z
|View full text |Cite
|
Sign up to set email alerts
|

Products of the OH Radical-Initiated Reaction of 3-Hexene-2,5-dione

Abstract: 3-Hexene-2,5-dione [CH3C(O)CH=CHC(O)CH3] and other unsaturated 1,4-dicarbonyls are formed from the atmospheric photooxidations of aromatic hydrocarbons. We have investigated the products of the gas-phase reaction of OH radicals with 3-hexene-2,5-dione in the presence of NO at room temperature and atmospheric pressure of air using in situ atmospheric pressure ionization tandem mass spectrometry. Products of molecular weight 102 and 191 were identified and from consideration of the potential reactions these are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 18 publications
0
14
2
Order By: Relevance
“…The variety of molecular structures of the DHO/OH reaction products, both identified and proposed, are due to multiple hydrogen abstraction sites on the DHO molecule, the carbon-carbon triple bond on one end of the DHO molecule, and the length of the carbon chain on the other end of the DHO molecule [39].…”
Section: Discussionmentioning
confidence: 99%
“…The variety of molecular structures of the DHO/OH reaction products, both identified and proposed, are due to multiple hydrogen abstraction sites on the DHO molecule, the carbon-carbon triple bond on one end of the DHO molecule, and the length of the carbon chain on the other end of the DHO molecule [39].…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Bethel et al (2001) has identified CH 3 C(O)CH(OH)CHO as a major product in the OH initiated oxidation of 3-hexene-2,5-dione and two decomposition pathways are assigned to the alkoxy radical:…”
Section: Degradation Of α β Unsaturated-γ -Dicarbonylsmentioning
confidence: 99%
“…268 Secondary organic aerosol models also differ for the CIT 255 and CAMx 269 models, while CMAQ and WRF-Chem models use the formulation of Schell et al 270 A Master Chemical Mechanism (MCM) is being constructed using a large set of kinetics and product data for the elementary reaction steps of the VOC oxidation process. 271,272 The process of aromatic HC oxidation is becoming better understood, [273][274][275][276][277][278] leading to MCM updates that have been evaluated against simulation chamber measurements. 279 -281 The MM5 282,283 and CALMET 284 meteorological models generate three-dimensional wind fields from basic physics and from observations.…”
Section: Air Quality Simulation Modelsmentioning
confidence: 99%